The Relationship of Interpersonal Intelligence with Student Learning Outcomes in The Subject of Characteristics at MIS Miftahul Hasanah - Pratiwi, Dela; Arbeni, Wawan (Jurnal Riset Ilmu Pendidikan, 2025)
This research was carried out by means of field research, namely collecting quantitative data. This research uses secondary data obtained from distributing questionnaires, with a sample size of 30 students. This research aims to determine the relationship between interpersonal intelligence and Aqidah Moral Learning Outcomes at MIS Miftahul Hasanah.  The learning outcomes of Class V students at MIS Miftahul Hasanah in the subject of moral beliefs are in the low category where after being classified, 26% got a score of 93-100, 43% of students got a score of 84-92, while 31% of students got a score of 75-83. The learning outcomes of Class V students in the subject of moral beliefs after using the interpersonal intelligence approach are included in the very category where after being classified 50% got a score of 93-100, 30% of students got a score of 84-92 , while 20% of students got a score of 75-83 . The relationship between interpersonal intelligence is related to the learning outcomes of class V moral beliefs at MIS Miftahul Hasanah. Based on the value of t_(count)(15,736) > t_table (1.69236). This is also supported by the coefficient of determination (R Square) of 92.9%, which shows that the independent variable interpersonal intelligence is able to explain 92.9% of changes in the dependent variable, namely learning outcomes of moral beliefs. Meanwhile, the remaining 7.1% is explained by variations or other factors not included in this research model. Based on the research results that have been described statistically, it can be seen that interpersonal intelligence is simultaneously positively related to the learning outcomes of class V moral beliefs at MIS Miftahul Hasanah